ANALISIS KEMAMPUAN RESILIENSI DALAM MENINGKATKAN KEMAMPUAN KONEKSI MATEMATIS SISWA - Abdurrahman Ansori (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2020)
This study to describe the ability of matehamtical resilience in improving students’ mathematical connection abilities. This research was conducted in the odd semester of the 2019/2020 school year. The population in this study were al students of class XI SMAN 21 Bekasi with a sample of the 30 students. The research instrument used was a test of mathematical connection ability test and student mathematical resilience questionnaire. The research method used is qualitative design and descriptive statical data analysis. Data were analyzed using data reduction, data presentation, and drawing conclusions. The result showed that : 1) students with high esilience had an average mathematical connection ability of 36%, 2) students with moderate resilience had an average mathematical connection of 34%, 3) students with low resilience had an average mathematical connection of 30% and 4) the results showed there were positive contributions of students with good mathematical resilience to students’ mathematical connection abilities.